The teak log volume estimation model for Sawn Timber: Case in Forest Management Unit (FMU) Bojonegoro – Perhutani – East Java - Indonesia. Issue 1 (July 2021) - Abdulah, L; Imanuddin, R; Utama, A P
Abstract: Cultivation of teak continues to be developed. The decision to harvest teak trees depends on the economic value. The economic value of the teak tree is the money value contained in the teak trunk which is divided into parts which are then called nodes. The determination of the part is based on the diameter size. Perhutani recognizes three classes of nodes namely A1 (10 - 19 cm), A2 (20 - 29 cm) and A3 (> 30 cm) and are expressed in the log volume table (TVL). Perhutani's TVL stated the relationship between tree circumference and log volume. This relationship is expressed in the estimator model and classified by nodes. To enter these numbers using constants that are difficult to account for. For this reason, this study aims to provide a volume estimator model for teak logs. The method used is a destructive method and regression analysis. The results showed that TVL in FMU can be explained based on the class of nodes but ignores the place of growth. The shape of the model is compound. This model works well at tree circumference intervals of 50 - 250 cm. Research like this needs to be propagated with wider tree circumference intervals.